The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.22379/2422402225
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia y factores de riesgo psicosociales de la depresión en un grupo de adultos mayores en Bogotá

Abstract: Introducción: la depresión es una enfermedad de alta prevalencia en adultos mayores. En Colombia su prevalencia se ha descrito entre 1,2 a 12% en mayores que viven en comunidad. Objetivo: estimar la prevalencia de depresión en un muestra de adultos mayores de Bogotá y describir los factores de riesgo psicosocial asociados. Material y métodos: se realizó un estudio de corte transversal observacional-descriptivo, en 889 adultos mayores autónomos. La depresión fue evaluada con el test de depresión ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
8
0
4
Order By: Relevance
“…La versión que se utilizó consta de 21 ítems, cada uno de ellos compuesto por varias afirmaciones sobre un mismo síntoma depresivo, que se presentan ordenados de menor a mayor gravedad y entre los cuales la persona evaluada debió escoger el que mejor describiera su estado; cada afirmación de los diferentes ítems evaluados se puntúa de 0 a 3. La interpretación de los resultados del test es la siguiente: altibajos considerados normales (1-10), leve perturbación del estado de ánimo (11)(12)(13)(14)(15)(16), estados de depresión intermitentes (17)(18)(19)(20), depresión moderada (21-30), depresión grave (31-40) y depresión extrema (> 40) (23).…”
Section: Materiales Y Métodosunclassified
“…La versión que se utilizó consta de 21 ítems, cada uno de ellos compuesto por varias afirmaciones sobre un mismo síntoma depresivo, que se presentan ordenados de menor a mayor gravedad y entre los cuales la persona evaluada debió escoger el que mejor describiera su estado; cada afirmación de los diferentes ítems evaluados se puntúa de 0 a 3. La interpretación de los resultados del test es la siguiente: altibajos considerados normales (1-10), leve perturbación del estado de ánimo (11)(12)(13)(14)(15)(16), estados de depresión intermitentes (17)(18)(19)(20), depresión moderada (21-30), depresión grave (31-40) y depresión extrema (> 40) (23).…”
Section: Materiales Y Métodosunclassified
“…Currently, late-life or elderly depression has been classified as a major public health problem due to its high prevalence (Yaka et al , 2014), its negative and devastating impact on quality of life and its association with higher mortality (WHO, 2017; Vink et al , 2008). Its origin is multicausal and is associated with psychosocial and biological risk factors (Salazar et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is higher among those with a higher level of education, such as undergraduate or graduate studies (61.6%), than those without education (45.2%) (Ministerio de Salud y Protección Social, COLCIENCIAS, Universidad del Valle Universidad de Caldas, 2016). A recent study in the city of Bogotá, reported 17% in the older adult population living in community, being higher among women (Salazar et al , 2015)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the main risk factors that are associated with the manifestation of geriatric depression are: belonging to the female gender (Chang et al, 2016;Salgado & Wong, 2007;Salazar et al, 2015;Torres et al, 2015); educational attainment; poor social support and scarce social participation (Segura-Cardona et al, 2015); perception of loneliness (Alpass & Neville, 2003); and the multiplicity of ways in which grieving processes manifest themselves (Kennedy, 2015). Physical risk factors include the following: difficulties in expedited locomotion and consequently a lack of autonomy (Campos et al, 2004); cognitive decline (Dillon et al, 2014); high prevalence of visual disability; and finally, previous history of depression (Bradley et al, 2016).…”
mentioning
confidence: 99%